Comparative analysis of performance and techno-economics for a H2O–NH3–H2 absorption refrigerator driven by different energy sources - Mohammad Omar, Abdullah; Tang, Chung Hieng (Elsevier Ltd., 2010)
The objectives of the present work are of two-folds. First, it evaluates the transient temperature performance of the H2O–NH3–H2 absorption cooling machine system’s components under two types of energy sources, i.e. the conventional electric energy from grid (electric) and fuel energy from liquid petroleum gas (LPG). Results obtained have shown that performance of various components under different type of energy sources is almost coherent. For the evaporator, the system with electric supply has shorter starting time, around 6 min earlier than the system run with LPG. Meanwhile, the system powered by LPG produced a lower cooling temperature around 9 C, compared to the system run with electric which produced temperature at around 7 C. Economical study had been carried out subsequently, for three different energy sources, i.e. electric, LPG and solar energy (photovoltaic). From the techno-economical analyzes, it was found that the conventional electric from grid is still the best form of energy source for short-term application, as far as the present location and conditions are concerned. LPG is the next attractive energy source, especially at locations with constant LPG supply; the photovoltaic energy from solar is attractive for long term consideration since it has zero fuel cost and environmentally-friendly, but with the highest initial cost